2022
DOI: 10.1371/journal.pone.0261786
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 is associated with higher risk of venous thrombosis, but not arterial thrombosis, compared with influenza: Insights from a large US cohort

Abstract: Introduction Infection with SARS-CoV-2 is typically compared with influenza to contextualize its health risks. SARS-CoV-2 has been linked with coagulation disturbances including arterial thrombosis, leading to considerable interest in antithrombotic therapy for Coronavirus Disease 2019 (COVID-19). However, the independent thromboembolic risk of SARS-CoV-2 infection compared with influenza remains incompletely understood. We evaluated the adjusted risks of thromboembolic events after a diagnosis of COVID-19 com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A cohort study from the US showed that COVID-19 was independently associated with a higher 90-day risk for venous thrombosis but not arterial thrombosis, compared with influenza. 11 Another study from Europe showed patients with influenza were more often diagnosed with arterial thrombotic complications than patients with COVID-19 infection. 12 Our analysis found that in-hospital stroke was higher in flu patients compared to COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study from the US showed that COVID-19 was independently associated with a higher 90-day risk for venous thrombosis but not arterial thrombosis, compared with influenza. 11 Another study from Europe showed patients with influenza were more often diagnosed with arterial thrombotic complications than patients with COVID-19 infection. 12 Our analysis found that in-hospital stroke was higher in flu patients compared to COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The illness can result in venous and arterial thrombosis, especially pulmonary embolism (PE) and microthrombi. A recent study on 417,975 COVID-19 and 345,934 influenza patients revealed that COVID-19 patients had higher venous thrombosis risk than influenza patients, but not arterial thrombosis [ 37 ]. The arterial thrombosis occurs in approximately 4% of critically ill COVID-19 patients—particularly in male, elder, and comorbid ones.…”
Section: Sars-cov-2 and Cardiovascular Systemmentioning
confidence: 99%
“…Notably, the incidence of major bleeding is not significantly higher in COVID-19 than in other critical illnesses [ 3 , 27 ]. This is intriguing because thrombotic events, especially pulmonary thromboembolism, have a higher incidence rate among patients with COVID-19 than in those with other acute illnesses [ 28 ]. This could be attributed to a COVID-19-specific coagulopathy characterized by in-situ formation of immune-thrombosis in the lungs [ 1 ].…”
Section: Discussionmentioning
confidence: 99%